2021
DOI: 10.1016/j.bios.2020.112709
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of SARS-CoV-2 antibodies using electrochemical impedance-based detector

Abstract: Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was classified as a pandemic by the World Health Organization and has caused over 550,000 deaths worldwide as of July 2020. Accurate and scalable point-of-care devices would increase screening, diagnosis, and monitoring of COVID-19 patients. Here, we demonstrate rapid label-free electrochemical detection of SARS-CoV-2 antibodies using a commercially available impedance sensing platform. A 16-well plate contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 28 publications
1
130
1
1
Order By: Relevance
“…Although they may present future use as point-of-care diagnostics, further work still needs to be done in order to miniaturize and lower the cost of these biosensors. Currently, optical, electrochemical, and molecularly imprinted biosensors are being designed for the detection of COVID-19 [143][144][145][146][147][148][149], as seen in Table 1:…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 Biosensorsmentioning
confidence: 99%
“…Although they may present future use as point-of-care diagnostics, further work still needs to be done in order to miniaturize and lower the cost of these biosensors. Currently, optical, electrochemical, and molecularly imprinted biosensors are being designed for the detection of COVID-19 [143][144][145][146][147][148][149], as seen in Table 1:…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 Biosensorsmentioning
confidence: 99%
“…The scheme representing the concept of SPCE/NPs/nano-Dendroids/GO/Ab probe fabrication to diagnose COVID-19 has been shown in Figure 4 B [ 100 ]. The label free electrochemical impedimetric sensor was prepared by Rashed et al to rapidly detect SARS-CoV-2 antibodies [ 101 ]. The sensor showed 100% accurate performance when results displayed by this sensor for clinical samples of COVID-19 negative and COVID-19 positive persons were compared with ELISA method.…”
Section: Biosensing Techniques For Sars-cov-2 Detementioning
confidence: 99%
“… Biosensor Pathogen Detection target Limit of detection Linear range Ref. EC SARS-CoV-2 S or N protein 19 ng/mL and 8 ng/mL - [ 103 ] EC SARS-CoV-2 Antibodies - - [ 101 ] EC SARS-CoV-2 N-gene 6.9 copies/Ī¼L 585.4 to 5.854 Ɨ 10 7 copies/Ī¼L [ 99 ] Cell-based SARS-CoV-2 Antigen 1 fgmL 1- 10 fg and 1 Ī¼g mL 1- [ 105 ] Optofluidic SARS-CoV-2 Antibody 0.5 pM 1- [ 83 ] Nanoplasmonic SARS-CoV-2 Virus particles 370 vp/mL 0 to 10 7 vp/mL [ 80 ] SPR SARS-CoV-2 Antibody 1.02 pM 2-1000 pM [ 82 ] LSPR SARS-CoV-2 RNA 1 pM 1 nM to 1 Ī¼M [ 106 ] Lateral flow optical/chemiluminescence SARS-CoV-2 Serum IgA - - [ 78 ] SERS-LFIA SARS-CoV-2 Antibody 1.28Ɨ10 7 -fold dilution - [ 79 ] Lateral flow SARS-CoV-2 RNA 12 copies...…”
Section: Biosensing Techniques For Sars-cov-2 Detementioning
confidence: 99%
“…Finally, the results obtained from impedance measurements were compared to ELISA results of the same serum samples, and it was reported that there was a strong correlation between them. The limit of this biosensing method's detection was not reported because of two reasons, hardware noise and sample handling variations [ 59 ].…”
Section: Biomarkers and Indicatorsmentioning
confidence: 99%